The trend forecaster's handbook. - Raymond, Martin, ....- (London : Laurence King, 2010)
The Trend Forecaster's Handbook is a sharp, in-depth and highly visual textbook and teaching aid for students and academics keen to know more about the world of trends, trend forecasting, and consumer-insight techniques. This "how to" book provides design students with skills to understand and track trends and use them to inform their research, design, and product development. With quotes, interviews, and case studies of key players.
Keywords: Design ; forcasting